Profesi Akuntan bagian dari Seni, Teknologi dan Sains - Antonius Juniarto; Hendrian Yonata; David Chrisdianto (LP2M STP Mataram, 2024)
The development of the era and the world of digitalization is becoming very fast, which is supported by technology that is increasingly dynamic and helps many people in every job. The role of accountants to be part of company performance reporting has a challenge which continues to be eroded by technology itself. The profession of being an accountant remains a pillar and can be a decision maker that is part of art, technology and also knowledge. There are so many views on accountants that create and enrich viewpoints. Service is carried out at Dian Bangsa Senior High School to provide students with new knowledge about the future, especially in the field of accounting and community service, which runs well and smoothly and is full of dynamics.